An Empirical Study of the Impact of Media Ownership on Political Bias and Public Opinion (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the impact of media ownership structures on political bias and public opinion. By examining the relationship between the concentration of media ownership and the extent of political bias in news coverage, as well as its effects on public attitudes, this research provides insights into how media ownership influences political perceptions. Utilizing a combination of quantitative and qualitative methods, the study reveals that a significant portion of respondents believes concentrated media ownership contributes to increased political bias and shapes public opinion. Findings indicate a prevailing concern about the effects of media control on news content, although there is considerable debate on the extent of this impact. The study highlights the need for policies that promote media diversity and transparency to ensure a more balanced and informed public discourse.